#### Answer

Net change: 4
Average rate of change: $\frac{4}{3}$

#### Work Step by Step

We find the net change from $x=-1$ to $x=2$:
$f(2)-f(-1)=6-2=4$
Next we find the average rate of change for this interval:
$\frac{f(2)-f(-1)}{2-(-1)}=\frac{4}{3}$

Published by
Brooks Cole

ISBN 10:
1305115546

ISBN 13:
978-1-30511-554-5

Net change: 4
Average rate of change: $\frac{4}{3}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.